Pengaruh Lingkungan Sekolah Terhadap Perilaku Beragama Siswa di MAN 1 Tulungagung Tahun Pelajaran 2020/2021 - Indah Kusuma Dewi (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
In addressing the moral degradation and today’s development, it is necessary for efforts in developing on the religious behavior of the students as a fortress in their daily life. This research was conducted in order to know how the influence of school toward religious behavior in MAN 1 Tulungagung in 2020/2021 academic year. This research is descriptive correlative research which describes the influence of school to the religious behavior of students in MAN 1 Tulungagung. Samples taken randomly by using Slovin formula as the results are 151 students. The instrument used in this research was a questionnaire and documentation. Data were analyzed using simple regression analysis. The research reveals that; The school environment contributes to religious behavior in MAN of Tulungagung district by 49.1%, This result suggests that to improve the quality of students' religious behavior can be done by instilling religious learning in the school environment.